On the presence of a well-established population of Symphodus melops (Linnaeus, 1758) in the central Mediterranean Sea with notes on its habitat and ecology - Tiralongo, Francesco (Array, 2018)
The presence of a well-established population of the corkwing wrasse, Symphodus melops (Linnaeus, 1758), is reported for the first time from the central Mediterranean Sea (southwestern Sicily). We discuss about the presence of the species in the area, with notes on its habitat, ecology and distribution.